Diet of the Wrinkle-Lipped Free-Tailed Bat (Chaerephon plicatus Buchannan, 1800) in Central Thailand - Supawan Srilopan (Prince of Songkla University, 2020)
Thesis (M.Sc., Ecology (International Program)--Prince of Songkla University, 2018